Unification and Coordination of Maritime Jurisdiction: Providing a Judicial Guarantee for International Trade and Marine Transport - Fu, Ben-Chao (Frontiers in Marine Science, 2022)
Maritime jurisdiction plays an important role in international trade and marine transport. It involves special kinds of rules that vary among different countries and legal systems. Thus, in international maritime jurisdiction, the coordination and settlements of jurisdictional conflicts are vital for the uniformity of international maritime law. This study provides a comparative analysis of maritime jurisdiction in international trade and marine transport. First, it introduces the concept, category, and legal characteristics of maritime jurisdiction based on historical sources. Then, we conduct a comparative analysis of the civil law system, common law system, international conventions, and Chinese maritime jurisdiction provisions, focusing on their differences and the existing legal problems. Among other suggestions for the improvement of the rules of maritime jurisdiction, this study proposes the unification and coordination of maritime jurisdiction, which could impact international trade and marine transport.